A Case Report of Subacute Combined Spinal Cord Degeneration Caused by Nitrous Oxide (‘Laughing Gas’) Abuse - Guk, J.; Valančienė, J.; Klimašauskienė, A. (Neurologijos seminarai, 2024)
Although nitrous oxide (N2O) has long been used as an anesthetic, it’s use as a recreational drug has recently increased. As N2O abuse is associated with a number of adverse health effects, it has become a significant public health issue. Chronic abuse can lead to a number of neurological complications, most commonly related to functional vitamin B12 deficiency. One of the most encountered forms of N2O neurotoxicity is a subacute combined degeneration, which can cause permanent neurological damage. The medical community should therefore be aware of the increasing scale of recreational N2O exposure and the possible complications of this drug abuse. Early recognition and treatment of N2O toxicity are crucial. We present the case of an 18-year-old male who was diagnosed with subacute combined spinal cord degeneration related to N2O abuse.